Uwarunkowania konkurencyjności małych i średnich przedsiębiorstw w "nowej" Unii Europejskiej - Pohulak-Żołędowska, Elżbieta (Competitiveness of small and medium sized enterprises in a "new" enlarged EU, 2005)
Small and medium sized enterprises are the backbone of modem market economies. The enlargement of the European Union brings new challenges for all member countries. One can easily see the differences between the New Member Countries SME’s sector and adequate enterprises of the EU-15. These differences have most of all historical background. The main question now is “do the enterprises have a chance to compete on the Common Market?”.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 45-53